Beneficial Effects of Pomegranate Peel Extract and Probiotics on Pre-adipocyte Differentiation - Sorrenti, Valeria; Randazzo, Cinzia Lucia; Caggia, Cinzia; Ballistreri, Gabriele; Romeo, Flora Valeria; Fabroni, Simona; Timpanaro, Nicolina; Raffaele, Marco; Vanella, Luca (Frontiers in Microbiology, 2019)
The beneficial effects of pomegranate are due to the ellagitannins and anthocyanins content, which are protective toward a wide variety of diseases including inflammatory diseases. Many investigators have reported that pomegranate waste (peel and seeds) extracts, made from waste product of industrial processing, show free radical scavenger and a potent antioxidant capacity. Pomegranate extracts (PEs) were also reported to possess noteworty antibacterial, antiviral, hypolipidemic, and anti-inflammatory bioactivities thanks to the polyphenolic compounds content, which includes punicalagins, gallic acid, and ellagic acid derivatives. The focus of the present manuscript was to study the prebiotic potentiality of a PE, soluble in water, and characterized through HPLC–PDA–ESI/MSn for its phenolic content. Moreover, since it has been reported that pomegranate extracts decreased the level of lipids in the blood and that a number of probiotic strains have been shown to affect adipogenesis in cell culture, this study was also performed to test the in vitro effects of PE and probiotic L. rhamnosus GG ATCC 53103 strain (LGG) on 3T3-L1 cell line. PE and probiotics substantially reduced the triglyceride content and intracellular lipid increase, compared to the control group. However, the combination treatment of PE and LGG filtered spent broth (SB) was the most effective in reducing triglyceride content and intracellular lipid accumulation. The mRNA expression levels of the main transcriptional factors implicated in adipocyte differentiation were substantially lower in 3T3-L1 cells treated with PE and LGG filtered SB. These results evidenced that a synergistic effect of probiotics and polyphenols contained in PE may affect in vitro adipogenesis and may contribute in development of new nutraceutical/probiotic-based remedies to prevent and to treat obesity.